Ocular signs and symptoms of orthokeratology patients associated with povidone iodine-based disinfecting solution. Issue 1 (February 2023) - Cho, Pauline; Boost, Maureen Valerie; Cheung, Sin Wan
Abstract: Purpose: To determine the frequency and severity of ocular symptoms and signs in new orthokeratology ( ortho -k) subjects using a povidone iodine (PI) disinfecting system compared to those present before lens wear, and whether these were associated with cleaning regimes. Methods: This study recruited 80 subjects from two myopia control studies, who used a PI disinfecting solution for routine use. Ocular symptoms and signs at baseline, one- and six-month after lens wear were reported via questionnaires and ocular examination, respectively. To determine if rates of occurrence were attributable to differences in cleaning regime, subjects were randomly assigned into four groups with respect to routine care procedures, which involved various combinations of rubbing and use of a daily and/or enzymatic cleaner. Results: Sixty-eight subjects completed all aspects of the study. As there were no significant differences in incidence of signs and symptoms between the four groups before and after lens wear (Friedman tests, p > 0.07), data were combined for further analysis. Prior to lens wear, itchiness (69 %) and dryness (53 %) were the most commonly reported symptoms. The frequency and severity of all symptoms remained similar after lens wear (p > 0.10). Presence of follicles in the lower tarsal conjunctiva (22 %) and conjunctival injection (15 %) was frequently observed, but reduced significantly after lens wear (p < 0.01). Mild corneal staining, noted in 13 % of subjects at baseline, did not change significantly over time (p = 0.17). Ocular signs were not necessarily reflected in symptoms and vice versa. Conclusion: Use of a PI-based solution did not increase the frequency or severity of ocular signs and symptoms observed before lens wear. Absence of a difference in occurrence of ocular discomfort with respect to cleaning regimes indicated that the use of the PI-based solution may adequately clean the lenses over a 6-month period.